2016
DOI: 10.1093/bja/aev544
|View full text |Cite
|
Sign up to set email alerts
|

Videolaryngoscopes: do they have role during rapid-sequence induction of anaesthesia?

T. Asai

Abstract: Simulated procedure rehearsal is more effective than a preoperative generic warm-up for endovascular procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This is especially useful for rapid sequence inductions and in patients at the risks of hypoxia and aspiration. [74] Fourth, during airway management training, the shared view on monitor can create a dynamic interaction, which facilitates teamwork and communication of the whole training team. This may stimulate enthusiasm of the students to learn intubation skill, improving the quality and outcomes of airway management training.…”
Section: Uescope and Tracheal Intubation Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially useful for rapid sequence inductions and in patients at the risks of hypoxia and aspiration. [74] Fourth, during airway management training, the shared view on monitor can create a dynamic interaction, which facilitates teamwork and communication of the whole training team. This may stimulate enthusiasm of the students to learn intubation skill, improving the quality and outcomes of airway management training.…”
Section: Uescope and Tracheal Intubation Teachingmentioning
confidence: 99%
“…This will provide the best care in any condition, assuring an acquirement in the experience and competence with techniques and an improvement in the comprehension of their limitations and value. [74] Recently, the use of VL as a standard care to replace DL for all tracheal intubations has been appealed by airway experts. [75]…”
Section: Uescope and Tracheal Intubation Teachingmentioning
confidence: 99%
“…Different cricoid forces may have to be used depending on the scenario as in children, obese, use of head up position, preanesthetic nasogastric tube in situ and with use of VLS. [1425] Zeidan et al showed the median cricoid force for female is 18.7 N (95% confidence interval 17.1–20.3) and 30.8 N (95% confidence interval 28.15–33.5) for males suggesting that median force necessary to occlude esophageal entrance to prevent regurgitation is less in women. [26] Oh et al showed that CP with increasing force resulted in a worse laryngeal view with Pentax AWS.…”
Section: Discussionmentioning
confidence: 99%
“…Though there was no statistical or clinical hemodynamic variations, the prolonged apnea time may cause hypoxia in patients with reduced oxygen reserve. [25] The use of a single design, broad channeled blade of KVL was also a limitation. The results would probably vary if non-channeled KVL blade was used as it is a thin blade that is easier to insert when the midpharyngeal space gets narrowed with the application of CP.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether tracheal intubation using a videolaryngoscope is less likely to traumatize the airway or to prolong apnea time, both of which may lead to serious airway complications [22]. Clarification of these would establish the true role of videolaryngoscopes in patients with difficult airways, particularly in patients receiving rapidsequence induction of anesthesia and in those undergoing emergency Cesarean section [27,28].…”
Section: Adequate Planningmentioning
confidence: 99%